Penyusunan Standart Operasional Prosedur Insiden Manajemen menggunakan Framework ITIL Versi 3: Studi kasus: Dinas Koperasi dan UKM Provinsi Jawa Timur - Ocha Taniya Brigidta; Siti Mukaromah; Asif Faroqi (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
The development of information technology has provided numerous benefits in the advancement of various organizations. One government organization that has implemented information technology to support its business processes is the Department of Cooperatives and SMEs of East Java Province. With the increasing number of information technology services used by the Department of Cooperatives, new challenges and consequences inevitably arise in the service maintenance process when an incident occurs with the information technology services. Unfortunately, the Department of Cooperatives appears to lack a clear procedure and guidelines for incident handling due to the absence of a related SOP. The purpose of this thesis is to formulate a Standard Operating Procedure related to incident handling that can be utilized by the Department of Cooperatives as a standard or reference, particularly in resolving incidents in information technology services. The SOP formulation uses the ITIL V3 framework because this framework includes the Service Operation domain, which contains the incident management process formulated based on best practices. Data collection for this thesis will be conducted through interviews and using the RACI Chart to determine the interviewees. This thesis results in 3 Standard Operating Procedures, 3 Record Documents, 1 Form, and 1 Priority Guide document, all of which are formulated based on the relevant framework and have been validated by the Department of Cooperatives and SMEs of East Java Province.